Whistleblowing and Corrupt Tendencies among Selected Employees in Three Public Organizations: Roles of Corruption Tolerance, Punishment Anxiety, and Neutralization - Ogungbamila, Bolanle; Osamika, Bamidele Emmanuel; Job, Emmanuel Dada (The Indonesian Institute of Science and Technology Research, 2024)
Anti-corruption efforts are often predicated on how to encourage whistleblowing and discourage corruption. To strengthen the anti-corruption drives, previous studies underscored the need for more research on psychological variables that may be connected with whistleblowing and corruption. This study, therefore, tested the extent to which employees in public sector service occupations are likely to engage in corruption and whistleblowing when they condone corruption, are less apprehensive about punishment, and can justify punishable work behaviors. This correlational study involved 331 employees (155 males; 176 females) of public sector organizations (110 health workers; 116 police personnel; 105 teachers), whose had a mean age of 43.01 years (SD = 7.86). They completed measures of corruption tolerance, punishment anxiety, workplace neutralization, whistleblowing intentions, and corrupt tendencies. Results of the 2-step hierarchical multiple regression analyses showed that whistleblowing intentions significantly reduced as employees condoned corruption, were afraid of punishment, and justified punishable work behaviors. Corrupt tendencies significantly increased as employees overlooked corruption and were able to justify punishable work behaviors, but decreased significantly as they became apprehensive of punishment. Based on these results, public sector organizations, especially the police, health, and education, should institute policies and implement psychological strategies that reduce the corruption-tolerant climate in the workplace; by increasing the fear of punishment for corruption and encouraging moral obligations to whistle-blow corruption among employees.